Improvement of tissue culture, genetic transformation, and applications of biotechnology to Brassica. Issue 1 (2nd January 2017) - Ravanfar, Seyed Ali; Orbovic, Vladimir; Moradpour, Mahdi; Abdul Aziz, Maheran; Karan, Ratna; Wallace, Simon; Parajuli, Saroj
Abstract: Development of in vitro plant regeneration method from Brassica explants via organogenesis and somatic embryogenesis is influenced by many factors such as culture environment, culture medium composition, explant sources, and genotypes which are reviewed in this study. An efficient in vitro regeneration system to allow genetic transformation of Brassica is a crucial tool for improving its economical value. Methods to optimize transformation protocols for the efficient introduction of desirable traits, and a comparative analysis of these methods are also reviewed. Hence, binary vectors, selectable marker genes, minimum inhibitory concentration of selection agents, reporter marker genes, preculture media, Agrobacterium concentration and regeneration ability of putative transformants for improvement of Agrobacterium -mediated transformation of Brassica are discussed.